O retiro em meio ao Parque Nacional da Serra do Cipó: lugar, normas, resistências, flexibilizações - Leonardo Vasconcelos de Souza (2017)
Protected areas have been consolidated as one of the main environmental protection policies adopted by the world. However, their adoption and deployment have caused conflicts with socio-spatial dynamics of the places where they are placed and imposed. Through my experi-ences with Brazilian protected areas, my concerns about how environmental norms may in-terfere in the configuration of these places have been increasing. To understand this situation, I turn to this dissertation on Retiro, place where Serra do Cipó National Park was created. My most specific experiences about Retiro were guided through qualitative research methodolo-gies, such as interviews with local residents and users, environmental managers and public prosecutors. I also made use of participant observation to understand part of the routine of retireiros and environmental managers. I have noticed that there are multiple dimensions interspersed in place, such as urbanization processes and tourist activities. However, I will focus here on the imposition of environmental standards highlighted during my experiences as more direct interference in the place. I concluded that, in a way, the regulations of the national park and the conduct of its management team are flexible and ensure the uses and occupations of the retireiros. However, some direct and subtle restrictions are still faced by the local families and, in front of them, these people take varying forms of resistance. The place Retiro, therefore, is not reconfigured only by the imposition of environmental standards, but also by the resistance of the retirees and the flexibility of the environmental managers regarding these norms. I therefore point out the need for conservation management instru-ments, such as the terms of commitments, to be adopted to better ensure the reconciliation between the interests of the retireiros and the environmental protection actions that, in view of my experiences, constitute the Retreat as a place.